Pengaruh Tax Avodance, Return on equity, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Muhammad Wafi Alhazmi; Dyah Pelitawati (Jurnal Simki Economic, 2026)
This study aims to analyze the effect of tax avoidance, return on equity, and firm size on firm value in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange during the period 2020–2022. This research uses a quantitative approach with secondary data obtained from audited annual financial statements. The sample was selected using purposive sampling. Data were analyzed using multiple linear regression supported by classical assumption tests. The results show that tax avoidance and return on equity do not have a significant effect on firm value, while firm size has a significant negative effect on firm value. Simultaneously, tax avoidance, return on equity, and firm size do not significantly affect firm value.